Investigation of Inflammatory Markers in Patients with Polycystic Ovary Syndrome Receiving and Not Receiving Metformin Treatment - Bulu, Aykut; Onalan, Erhan; Yakar, Burkay; Bulu, Guelay; Yildirim, Senanur Onalan; Ugur, Kader; Donder, Emir (Mdpi, 2025)
Background and Objectives: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age. The etiology of PCOS is complex and is associated with low-grade chronic inflammation. The current study aimed to investigate inflammation markers in PCOS patients with and without metformin treatment. Materials and Methods: This cross-sectional study included 30 age-matched PCOS patients not receiving metformin treatment, 50 PCOS patients receiving metformin treatment, and 30 healthy controls. The groups were compared according to inflammatory (hs-CRP, NLR, and PLR) and metabolic parameters (lipids, fasting blood-sugar insulin, HOMA-IR). Results: Insulin (p < 0.001) and HOMA-IR (p < 0.001) score median values of PCOS patients were found to be significantly higher than the control group. CRP levels of PCOS patients receiving metformin treatment were found to be higher than both control and PCOS patients not receiving metformin treatment (p < 0.001). There was a significant difference between the groups in terms of PLR mean value (p = 0.031). The mean PLR value of PCOS patients, both those receiving metformin treatment and those not receiving treatment, was found to be significantly higher than the control group. In PCOS patients not receiving metformin treatment, there was a negative significant correlation between NLR and HDL level (r: -0.384; p: 0.036), NLR and insulin (r: 0.422; p: 0.020), and HOMA-IR score (r: 0.439; p: 0.015). There was a positive significant correlation between them. Conclusions: In the current study, PLR was significantly increased in all PCOS patients compared to controls. CRP levels in PCOS patients receiving metformin treatment were significantly higher than both control and untreated PCOS patients. PLR is positively associated with insulin and HOMA-IR scores in PCOS patients.
Keywords: polycystic ovary syndrome; inflammation; C-reactive protein; NLR; PLR